Character Education Through Gender Wayang Learning - I Made Luwih (Jayapangus Press, 2021)
This study aimed to determine the character education in Gender Wayang learning. The method used in this study was a qualitative research method. It was more revealing the situation, which was the phenomenon directly the object under study. Data collection techniques were conducted using observation, interviews, documentation, and literature studies. The study results were (1) The process of implementing Gender Wayang learning in schools consists of preparation, delivery, training, and performance stage. (2) The results of implementing Gender Wayang learning in schools were measured using an assessment rubric. (3) The value of character education in Gender Wayang learning includes educational, religious, and social life values.